2014
DOI: 10.1016/j.ijhm.2013.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Thinking job embeddedness not turnover: Towards a better understanding of frontline hotel worker retention

Abstract: This article reports the findings of a study of 327 Australian hotel frontline employees using a survey of job embeddedness. The research provides a novel application of the job embeddedness construct to the hospitality industry, not only validating the factor structure of the job embeddedness scale, but also investigating the relationship between job embeddedness and other job-related attitudes that influence employee turnover. Findings indicated that a six factor solution is the best explanation. Testing a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
123
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 142 publications
(137 citation statements)
references
References 60 publications
6
123
0
8
Order By: Relevance
“…A relationship exists between job embeddedness and worker intention in the Australian hospitality industry (Robinson et al, 2014). Robinson et al (2014) gathered data from 327 frontline employees from varying hotels and found that several dimensions of job embeddedness could explain turnover and retention.…”
Section: Engagement and Embeddednessmentioning
confidence: 99%
See 3 more Smart Citations
“…A relationship exists between job embeddedness and worker intention in the Australian hospitality industry (Robinson et al, 2014). Robinson et al (2014) gathered data from 327 frontline employees from varying hotels and found that several dimensions of job embeddedness could explain turnover and retention.…”
Section: Engagement and Embeddednessmentioning
confidence: 99%
“…Robinson et al (2014) gathered data from 327 frontline employees from varying hotels and found that several dimensions of job embeddedness could explain turnover and retention. In particular, dimensions of organizational sacrifice and community positively shaped organizational commitment.…”
Section: Engagement and Embeddednessmentioning
confidence: 99%
See 2 more Smart Citations
“…I did not consider these measures suitable due to their length and potential for overlap with other constructs that are also the subject of the current study. Accordingly, I measured job satisfaction using a three-item global measure adapted from Cammann, Fichman, Jenkins and Klesh (1983) that has been extensively used in organisational research (e.g., Andrews & Kacmar, 2001;Ashforth & Saks, 1996;Gregory, Albritton & Osmonbekov, 2010;Robinson et al, 2014;Saks, 2006;Valentine & Fleischman, 2008). A sample item is "All in all, I am satisfied with my job".…”
Section: Job Satisfaction and Affective Organisational Commitmentmentioning
confidence: 99%